Dispersion of Benthic Plumes in Deep-Sea Mining: What Lessons Can Be Learned From Dredging? - Helmons, Rudy; de Wit, Lynyrd; de Stigter, Henko; Spearman, Jeremy (Frontiers in Earth Science, 2022)
Over the past decade, deep-sea mining has received renewed interest due to scarcity of raw materials. Deep sea mining has been spurred by the need for critical resources to support growing populations, urbanization, high-tech applications and the development of a green energy economy. Nevertheless, an improved understanding of how mining activities will affect the deep sea environment is required to obtain more accurate assessment of the potential environmental impact. In that regard, the sediment plumes that are generated by the mining activity have received the highest concern, as these plumes might travel for several kilometers distance from the mining activity. Various plume sources are identified, of which the most profound are those generated by the excavation and collection process of the seafloor mining tool and the discharge flow to be released from the surface operation vessel after initial dewatering of the ore. In this review, we explore the physical processes that govern plume dispersion phenomena (focusing in the main on benthic plumes), discuss the state of the art in plume dispersion analysis and highlight what lessons can be learned from shallow water applications, such as dredging, to better predict and reduce the spread and impact of deep sea mining plumes.